THE EFFECT OF ENTREPRENEURIAL KNOWLEDGE ON ENTREPRENEURIAL INTENTION WITH THE MEDIATION OF ENTREPRENEURIAL ATTITUDES, SUBJECTIVE NORMS, AND SELF- EFFICACY - Iskandar Iskandar; Yuli Yuliati; Yeyen Suryani; Sri Mulyati (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2023)
The results of pre-research conducted by researchers by giving a questionnaire regarding entrepreneurial intentions to students, revealed that the entrepreneurial intentions of students at SMK Palasah District are still low. Various efforts can be made to increase entrepreneurial intentions, one of which is by learning entrepreneurial creative products. In addition to entrepreneurial knowledge, other internal factors such as attitudes, subjective norms and self-efficacy also affect the level of entrepreneurial intentions. The population in this study were all XII grade students of SMKN 1 Palasah and SMKS Ar Rahmat which amounted to 913 people with a sample proportion of 278 students. The results showed that 1) Entrepreneurial knowledge has a direct and positive effect on entrepreneurial intention. 2) Entrepreneurial attitudes mediate the influence of entrepreneurial knowledge on entrepreneurial intentions. 3) Subjective norms mediate the effect of entrepreneurial knowledge on entrepreneurial intentions. 4) Self-efficacy mediates the effect of entrepreneurial knowledge on entrepreneurial intention.